High Lability Fe Particles Sourced From Glacial Erosion Can Meet Previously Unaccounted Biological Demand: Heard Island, Southern Ocean - van der Merwe, Pier; Wuttig, Kathrin; Holmes, Thomas; Trull, Thomas W.; Chase, Zanna; Townsend, Ashley T.; Goemann, Karsten; Bowie, Andrew R. (Frontiers in Marine Science, 2019)
Iron (Fe) is an essential micronutrient that controls phytoplankton growth in the Southern Ocean. Dissolved Fe (< 0.4µm) has been extensively studied due to its relatively high bioavailability. However, particulate Fe (> 0.4µm) is far more abundant and may also become bioavailable through biogeochemical processing. To assess natural Fe fertilisation from the particulate fraction, we surveyed suspended particles in the water column at 11 stations in the vicinity of Heard and McDonald Islands (HIMI), in the Indian sector of the Southern Ocean and compared these to downstream plateau and reference stations. We quantified the labile (potentially bioavailable) fraction using a chemical leach. Suspended particles sourced from glacial erosion and fluvial outflow, including nanoparticulate Fe oxides near Heard Island, contained a significantly higher fraction of labile Fe (18 ± 2.8% of total Fe, or 115 ± 34 nM, n = 9) than all other coastal areas surveyed. In contrast, waters around McDonald Island, proximal to diffuse gasohydrothermal sites, contained poorly labile, highly refractory titanium and Fe bearing minerals such as ilmenite. We conclude that glacial erosion of Heard Island in combination with a unique elemental signature of the source rock, is an important mechanism of Fe supply to downstream waters. Our calculations show that the labile Fe supplied from primarily glacial erosion on Heard Island is sufficient to satisfy previously unmet estimates of phytoplankton demand for the region, and therefore critical to the area’s productivity. As we move into a world facing major ecosystem shifts under a changing climate, it is important to understand those ecosystem services that may change into the future. At the current rate of glacier retreat, this ecosystem service of glacial erosion and Fe supply to coastal waters will cease with the eventual loss of glacial cover with direct impacts for this historically highly productive region.